Synthesis of high-performance photocatalysts for solar-driven hydrogen production and carbon dioxide reduction - Chan Woo Lee; Jeong Hyun Kim; Megalamane S. Bootharaju; Taeghwan Hyeon; Byoung-Hoon Lee (Carbon Future)
Photocatalysis presents a promising pathway for clean energy generation by leveraging solar energy under environmentally benign conditions with minimal pollutant emissions. However, its widespread application is hindered by low catalytic efficiency, stemming from limited light absorption, rapid recombination of photo-excited electrons, and suboptimal charge carrier potential for target reactions. This review discusses advanced strategies to enhance photocatalytic performance by modulating photocatalytic supports and refining co-catalysts. Techniques such as hydrogenation and extrinsic doping of photocatalytic supports are highlighted for their ability to broaden light absorption and prolong electron lifetimes. Additionally, the strategic design of co-catalysts, including the use of nanoclusters and atomically dispersed catalysts, is emphasized for optimizing charge carrier potential and improving atomic utilization efficiency. This review aims to guide researchers in developing high-performance photocatalysts for clean energy applications, including CO2 reduction and plastic waste photoreforming, thereby contributing to the advancement of sustainable energy technologies.